Meningkatkan Aktivitas, Rasa Ingin Tahu, Dan Hasil Belajar Muatan PPKn Pada Peserta Didik Menggunakan Model Provit Di Kelas Iv SDN Pangeran 1 Banjarmasin - Desy Rahmayati; Fathul Jannah; Akhmad Riandy Agusta; Ari Hidayat (GLOBAL SCIENTS PUBLISHER, 2024)
The problem in the study lies in the lack of student activity and low curiosity of students which also affects student learning outcomes in Civics content with Theme 7 Beautiful Diversity in My Country. One of the efforts to overcome these problems is to use a combination of Problem Based Learning, Somatis Auditori Visual Intelektual, Think Talk Write learning models. The purpose of this study was to describe the activities of educators and analyze the increase in learner activities, student curiosity and student learning outcomes. This research used Classroom Action Research (PTK) which was conducted in 3 meetings. The subjects of this study were fourth grade students of Prince 1 Banjarmasin, totaling 20 students in semester II of the 2023/2024 school year. Data were analyzed qualitatively through observations, namely educator activities, learner activities, curiosity, then quantitative data were analyzed for student learning outcomes through written tests in groups and individuals. The data was analyzed with descriptive techniques and described in the form of tables and graphs. The results of this study indicate that the teacher's activities were carried out